A factorial design for the evaluation of the optimal conditions for LiCoO2 particles dissolution - Acedo-Bueno, Luis Fernando; Cerrillo-González, María del Mar; Villén-Guzmán, María Dolores; Arhoun, Brahim; Paz-García, Juan Manuel; Rodríguez-Maroto, José Miguel (My University, 2020)
The hydrometallurgical leaching process for the recovery of valuable metals from the cathode active materials of spent lithium batteries was evaluated. Experiments were carried out using LiCoO2 which is one of the most used cathodes in lithium-ion batteries. With the aim of optimizing the most relevant parameters (solid to liquid ratio, the concentration of the extracting agent and the concentration of the reducing agent) for the extraction process, a factorial experimental design was carried out to evaluate the effect of them in the dissolution process. Batch experiments were performed using 0.1 and 1 M HCl solution as extracting agent, solid to liquid ratio of 5 and 50 g L–1 and in absence and presence of reducing agent, i.e. 5% H2O2. The kinetic of LiCoO2 dissolution was studied in batch experiments using as extracting agent 2.5 M of HCl, achieving an extraction of 52% and 87% of cobalt and lithium, respectively.
Keywords: Baterías de litio; Baterías de iones de litio; LiCoO2; Materias primas críticas; Extracción